INTEGRATING ETHICAL AND FAITH BASED VALUES IN SOCIAL LIFE : A Hadith Perspective of Shaykh Nawawi al-Bantani in Qāmi’ al-Ṭuġyān - Fahmi Andaluzi; Irfan Padlian Syah; Abdul Fatah (AL ISNAD: Journal of Indonesian Hadith Studies, 2025)
This Morality is an important part of the teachings of Islam where morality is included in the scope of faith and is classified as a discussion of monotheism. This article seeks to examine the discussions of morality in the book Qāmiʻ al-Ṭuġyān by Sykeh Nawawi al-Bantani The method used in searching for data in this study is the library research method by collecting primary and secondary reference sources, the author uses the book Qāmiʻ al-Ṭuġyān as a primary source while for secondary sources use books or other articles that are relevant to the discussion. For the discussion in this article, the author uses a descriptive-analytical method, namely by first describing the discussion of morality in the book Qāmiʻ al-Ṭuġyān and then analyzing the data obtained. The results of this study show that morality is a very important part of Islamic teachings, in the book Qāmiʻ al-Tuġyān morality includes two important themes, first, a person's attitude towards Allah SWT and His Messenger, namely by carrying out his commands and staying away from his prohibitions and carrying out his sunnahs, second, morality is also a person's attitude in social life, namely having a gentle heart, full of affection, being kind to neighbors, honoring guests and the community.